Reducing field emission in superconducting cavities with ozone - Roger Ruber (Physical Review Accelerators and Beams)
Contaminations on the active surface of high-power microwave resonators, such as radio-frequency accelerator cavities, can greatly enlarge electron field emission and reduce their performance. In this work, we demonstrate the use of ozone to clean the surface of niobium superconducting radio-frequency cavities resulting in reduced field emission and enhanced accelerating gradient before onset of field emission. We report results from processing four cavities.